Intraconversion of Polar Ginsenosides, Their Transformation into Less-Polar Ginsenosides, and Ginsenoside Acetylation in Ginseng Flowers upon Baking and Steaming - Xiang Li; Fan Yao; Hang Fan; Ke Li; Liwei Sun; Yujun Liu (Molecules, 2018)
Heating is a traditional method used in ginseng root processing, however, there aren’t reports on differences resulting from baking and steaming. Moreover, ginseng flowers, with 5.06 times more total saponins than ginseng root, are not fully taken advantage of for their ginsenosides. Transformation mechanisms of ginsenosides in ginseng flowers upon baking and steaming were thus explored. HPLC using authentic standards of 20 ginsenosides and UPLC-QTOF-MS/MS were used to quantify and identify ginsenosides, respectively, in ginseng flowers baked or steamed at different temperatures and durations. Results show that baking and steaming caused a 3.2-fold increase in ginsenoside species existed in unheated ginseng flowers (20/64 ginsenosides) and transformation of a certain amount of polar ginsenosides into numerous less polar ginsenosides. Among the 20 ginsenosides with standards, polar ginsenosides were abundant in ginseng flowers baked or steamed at lower temperatures, whereas less polar ginsenosides occurred and were enriched at higher temperatures. Furthermore, the two types of heating treatments could generate mostly similar ginsenosides, but steaming was much efficient than baking in transforming polar- into less polar ginsenosides, with steaming at 120 °C being comparably equivalent to baking at 150 °C. Moreover, both the two heating methods triggered ginsenoside acetylation and thus caused formation of 16 acetylginsenosides. Finally, a new transformation mechanism concerning acetyl-ginsenosides formation was proposed.